Sixty years of research on technology and human resource management: Looking back and looking forward. Issue 1 (18th November 2020) - Kim, Sunghoon; Wang, Ying; Boon, Corine
Abstract: Technology has changed the way we work and how companies manage their employees. This article reviews 60 years of research on the relationship between technology and human resource management, as represented in Human Resource Management . Based on 154 articles, we identify recurring and evolving patterns of research on technology across three time periods (separated by the advent of the personal computer in 1977 and by the popularization of consumer internet services in 1997), three perspectives on technology (tool, proxy, and ensemble view of technology), and three thematic streams (the impact of technology on jobs and organizations, the utilization of technology in HR activities, and the management of technology workers). Drawing on patterns of research that emerged in the past, we provide suggestions for future HR research on newly arriving technology.